Dirva company - Žukas, Vladas (Knygotyra, 1992)
„Dirva" company, which operated during 1918-1940 in Kaunas and Marijampolė, is one of the most renowned publishing houses of the Republic of Lithuania. Adomas Dundzila and Bronius Širutis were the founders and owners of the company. It had a publishing house and a printing house in Marijampolė, as well as bookshops in Marijampolė, Kaunas, and from 1939, in Vilnius. The production of the „Dirva" company included 546 books. At different periods (e.g., 1931), the company was considered the most efficient publishing house in Lithuania. The main areas of publishing activities for this house were: manuals for schools (24%), children’s literature (about 15%), and fiction (25%). The remaining publications included academic works, popular-scientific literature, reference books, musical scores, and fine art editions. Original books were predominant, with the company publishing over one hundred author books. „Dirva" contributed significantly to the development of typographic and artistic culture in Lithuanian book publishing (through its printing house) and book distribution (through its bookshops). The proprietors of the company managed to achieve a synthesis of commercial and cultural activities. In July-September 1940, the printing house (estimated at 750,000 litas) and bookshops were nationalized.